2001
DOI: 10.1111/j.2042-7174.2001.tb01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of psychosocial factors which influence patient adherence with antihypertensive medication

Abstract: Focal points □ It is estimated that only 50 per cent of hypertensive patients adhere to medication regimens □ In this study evaluation of self‐efficacy and the theory of planned behaviour was used to identify psychosocial factors which impact on patient adherence to antihypertensives □ High self‐efficacy, intentions to comply with the medication regimen, possessing a positive attitude towards taking medication, perceiving pressure from significant others to take medication as prescribed, and perceiving control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 1 publication
4
14
1
Order By: Relevance
“…Indeed, only about 5% of patients claimed disclosure of the financial difficulties they were experiencing with purchase of their medicines. This suggests lack of patients' involvement in the therapeutic planning/choice of drug therapy process, a key factor that has been identified as strong determinant of non-adherence to drug therapy [23]. The probable negative contributions of non-adherence to drug therapy to rising morbidity and mortality figures especially among patients with chronic medical conditions are well documented.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, only about 5% of patients claimed disclosure of the financial difficulties they were experiencing with purchase of their medicines. This suggests lack of patients' involvement in the therapeutic planning/choice of drug therapy process, a key factor that has been identified as strong determinant of non-adherence to drug therapy [23]. The probable negative contributions of non-adherence to drug therapy to rising morbidity and mortality figures especially among patients with chronic medical conditions are well documented.…”
Section: Discussionmentioning
confidence: 98%
“…Adherence is dependent on numerous factors and has been shown to vary from 0 to 100% in different populations studied [12], [13], [14], [15]. Factors such as age [16], [17], gender [18], low socioeconomic status and severity of disease [17], class of drug prescribed [19], number of pills per day [16], [18], side effects of medication [16], [17], patient's inadequate understanding of the disease and importance of the treatment [16], [17], co-morbid medical conditions [17], lack of social support [20], poor patient-provider relationship [21], cost, forgetfulness [22], and presence of psychological problems, especially depression [17], [21], have all been shown to affect adherence in various populations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Ogedegbe et al (2003) found an association between low income and medication, adherence self-efficacy among African Americans. Finally, Lennon, Hughes, Johnston, and McElnay (2001) conducted a study in an outpatient clinic in which a significant relationship was observed between self-efficacy scores and self-reported medication adherence (p < .005).…”
Section: Medication Adherence Self-efficacymentioning
confidence: 99%